THE USE OF MIND MAPPING ON IMPROVING STUDENTS??? WRITING ABILITY AT TENTH GRADE OF SMAN 7 KOTA TANGERANG IN THE ACADEMIC YEAR OF 2018/2019 - Kamelia .; Hiqma Nur Agustina; Imam Sudarmaji (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2018)
The objective of this study is to find the use of mind mapping on improving students??? writing ability, especially for biographical recount text at the tenthgrade students of SMAN 7 Kota Tangerang in the academic year of 2018/2019.The sample of this study were 35 students. This study used quantitative method with pre ??? experimental design by using one group pre ???test and post ??? test. The result of the research shows that there is a significant difference in student???s writing ability between tenth grade students of SMAN 7 Kota Tangerang before and after taught using the mind mapping technique. It can be seen in the result of the study, the average pre ??? test score of experiment class students is 68.26 and the average post ??? test score of experiment class students is 85.40. It means that there is a significant difference in students??? writing ability between tenth grade students of SMAN 7 Kota Tangerang before and after taught using the mind mapping technique. The research hypothesis is proven that using mind mapping technique in teaching writing especially in recount text makes the students??? writing score higher.